Deformable image registration and interobserver variation in contour propagation for radiation therapy planning. (8th May 2016) - Riegel, Adam C.; Antone, Jeffrey G.; Zhang, Honglai; Jain, Prachi; Raince, Jagdeep; Rea, Anthony; Bergamo, Angelo M.; Kapur, Ajay; Potters, Louis
Abstract : Deformable image registration (DIR) and interobserver variation inevitably introduce uncertainty into the treatment planning process. The purpose of the current work was to measure deformable image registration (DIR) errors and interobserver variability for regions of interest (ROIs) in the head and neck and pelvic regions. Measured uncertainties were combined to examine planning margin adequacy for contours propagated for adaptive therapy and to assess the trade‐off of DIR and interobserver uncertainty in atlas‐based automatic segmentation. Two experienced dosimetrists retrospectively contoured brainstem, spinal cord, anterior oral cavity, larynx, right and left parotids, optic nerves, and eyes on the planning CT ( CT 1 ) and attenuation‐correction CT of diagnostic PET/CT ( CT 2 ) for 30 patients who received radiation therapy for head and neck cancer. Two senior radiation oncology residents retrospectively contoured prostate, bladder, and rectum on the postseed‐implant CT ( CT 1 ) and planning CT ( CT 2 ) for 20 patients who received radiation therapy for prostate cancer. Interobserver variation was measured by calculating mean Hausdorff distances between the two observers' contours. CT 2 was deformably registered to CT 1 via commercially available multipass B‐spline DIR. CT 2 contours were propagated and compared with CT 1 contours via mean Hausdorff distances. These values were summed in quadrature with interobserver variation for margin analysis and compared with interobserver variation for statistical significance using two‐tailed t ‐tests for independent samples ( α = 0.05 ). Combined uncertainty ranged from 1.5‐5.8 mm for head and neck structures and 3.1‐3.7 mm for pelvic structures. Conventional 5 mm margins may not be adequate to cover this additional uncertainty. DIR uncertainty was significantly less than interobserver variation for four head and neck and one pelvic ROI. DIR uncertainty was not significantly different than interobserver variation for four head and neck and one pelvic ROI. DIR uncertainty was significantly greater than interobserver variation for two head and neck and one pelvic ROI. The introduction of DIR errors may offset any reduction in interobserver variation by using atlas‐based automatic segmentation. PACS number(s): 87.57.nj, 87.55.D‐